Optimisation of solid-liquid extraction of bioactive compounds from Orthosiphon stamineus benth leaves - Abdul Razak, Mohd Farhan (2012)
Orthosiphon stamineus, also known as Misai Kucing, is one of the invaluable medicinal plants originated from Southeast Asia. O. stamineus leaves were used in plenty of applications related to the medicinal purposes and are believed to cure certain disease such as hypertension, gout and fever. However, very little research done with regards to ascertain optimum extraction process and quality extract of O. stamineus leaves. This research studied a solid- liquid extraction (SLE) process which are involved in processing of bioactive extract from O. stamineus leaves. Different experiments were carried out to determine the effects of various operating parameters on the qualitative and quantitative aspects of O. stamineus leaves. Rosmarinic acid (RA) and Sinensetin (SEN) were selected as the quality indicators of the product because these two compounds were played a major role in the bioactivities including anti- inflammatory, anti- oxidant and anti- pyretic of O. stamineus leaves. Water is most suitable solvent for extracting O. stamineus leaves compared to ethanol, ethyl acetate, and hexane. This was because water gave the highest extraction yield as well as quality extract that related to RA and SEN. Besides, water also indicated highest antioxidant and anti- inflammatory compared to other solvents. The optimum extraction condition of O. stamineus leaves was determined as 60°C and the ratio of water to solid is 10:1 (ml:g) to avoid degradation of SEN based on analysis using Response Surface Methodology (RSM) technique. of 6 hours were found to be optimum based on analysis of Response Surface Methodology (RSM). Two hours of extraction duration was selected as optimum extraction time based on kinetic study. The activation energy of the extraction is 36.57 kJ mol-1.